Determinants of cyberattack prevention and the role of cybersecurity leadership in UAE banking sector - Alshamsi, Sultan Khalifa Humaid Khalifa (2023)
Today's organized criminal groups focus on easy ways to make money, ways that target rich organizations because a large amount of money flows daily and contains sensitive information. Cyberattack prevention factors have a significant impact on the perception of social and moral values in the business context. Moreover, cyberattacks have become a crucial matter among world's developed countries as well as developing countries like UAE. Therefore, there is a need to study the role of skilled leaders in financial organizations in the UAE in preventing cyberattacks and investigate other human factors related to the individual in financial organizations in UAE in preventing cyberattacks. A general perception of the research is to propose a research framework for cyberattack prevention in the UAE by employing the Protection Motivation Theory and adding new variables focusing on the role of an organization's cybersecurity leadership, frequent training, and the role of government frequent alerting. A proposed framework and 22 hypotheses were constructed to guide this study. This research employed a quantitative research method. The data were collected from 310 financial executive officers from a commercial bank in the Central Bank, an industrial bank in the Emirates Industrial Bank, a merchant bank in the Ajman Bank, and an Islamic bank in the ADIB bank of the UAE that use digital technology to enhance their daily banking operation through survey questionnaires. Subsequently, the data were analyzed using Structural Equation Modelling (SEM) as a statistical methods and techniques approach. The results indicated a significant association between all investigated independent variables and cybersecurity leadership, and cybersecurity leadership mediates the relationship between investigated independent variables and cyberattack prevention. No significant association was shown between investigated independent variables and cyberattack prevention, except (H4&H7) that show a significant association. Although UAE government regularly applies and invests in many technical measures to prevent cyberattack in both individual and organizational levels, many U AE financial firms have been identified as high-level targets in cyberattacks in this digital transformation era. The coefficient in cybersecurity leadership might be viewed as a prevention element for cyberattacks based on the findings. With greater cybersecurity leadership success, the implementation of cyberattack prevention increases. This study emphasizes the importance of cybersecurity leadership in a cyberspace environment that protects against cyberattacks and promotes cybersecurity awareness within a financial organizations and society in U AE. The research framework contributes to the development of cyberattack prevention by encouraging cybersecurity leadership in setting cybersecurity strategy, positioning cybersecurity functions, and implementing cybersecurity activities through protection motivation theory that emphasizes (1) threat appraisal that guarantees security guidelines are reasonable and seen for the organizational climate and (2) coping appraisal that guarantees threat data is joined by useful data in deferring it, which is appropriate for this research setting in a banking climate, (3) leadership's important role in leveraging and fostering cyberattack prevention in UAE financial sector.